Proteomic and phosphoproteomic analysis of rabies pathogenesis in the clinical canine brain and identification of a kinase inhibitor as a potential repurposed antiviral agent. - Peerut Chienwichai; Kunjimas Ketsuwan; Boonlert Lumlertdacha; Chanon Fa-Ngoen; Punchaya Supasawat; Rojjanaporn Pulmanausahakul; Promsin Masrinoul; Tipparat Thiangtrongjit; Onrapak Reamtong (PLoS ONE, 2025)
Rabies is a fatal zoonosis caused by the rabies virus (RABV) that has afflicted humans for thousands of years. RABV infection leads to neurological symptoms and death; however, its pathogenesis in the brain is unclear, which complicates patient care. Given that no treatment exists for symptomatic cases, there is an urgent need for effective antiviral drugs. In this study, we aimed to investigate the pathogenic mechanism of RABV in the brain and screen for potential anti-RABV drugs. Protein samples were extracted from the brains of RABV-positive and RABV-negative dogs, and proteomic and phosphoproteomic analyses were conducted. The results showed that the synaptic vesicle cycle is critical to RABV pathogenesis. The kinases involved in the phosphorylation of proteins in the synaptic vesicle cycle were identified and examined as potential drug targets. Casein kinase 2 and protein kinase C were found to be key kinases for RABV replication, and five inhibitors of these enzymes were tested for their anti-RABV properties. Pretreating cells with the kinase inhibitor sunitinib significantly reduced the viral yield after RABV infection. Our findings suggest that RABV interferes with synaptic communication, which leads to rabies, and that inhibiting a vital kinase can reduce viral production. Hence, our findings have implications for the development of rabies treatment regimes.